2021
DOI: 10.1111/vsu.13705
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo comparison ofhand‐suturedversus circular stapled anastomosis in canine large intestine

Abstract: Objective To compare leakage pressures of colonic anastomoses performed with circular staplers to conventional hand‐sewn techniques in dogs. Study design Ex‐vivo study. Animals Colon from 11 canine cadavers. Methods Thirty‐two colonic anastomoses were performed. Four segments from each colon were randomly assigned to one of four techniques: hand‐sewn colonic anastomoses performed with 4‐0 glycomer 631 (G) and 4‐0 barbed glycomer 631 (BG), and circular stapled colonic anastomoses using 4.8 mm End‐to‐End Anastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Samples were immediately tested after completion of the anastomosis following a previously published technique 14,15 . An 11 cm long, 8 Fr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were immediately tested after completion of the anastomosis following a previously published technique 14,15 . An 11 cm long, 8 Fr.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were immediately tested after completion of the anastomosis following a previously published technique. 14,15 An 11 cm long, 8 Fr. introducer (Super Arrow-Flex Introducer Set; Arrow International, Inc., Reading, Pennsylvania) was inserted in the urethra and secured with two circumferential sutures using 3-0 Glycomer 631 (Biosyn, Medtronic, Minneapolis).…”
Section: Pressure Testingmentioning
confidence: 99%
“…Our data show that the inverting Cushing suture withstands higher luminal pressures. Other studies that compared initially the leak pressure of four anastomosis technique (1) handsewn anastomosis (HSA), (2) barbed suture anastomosis (B-HSA), (3) stapled functional end-to-end anastomosis (SFEEA), and (4) stapled functional end-to-end anastomosis with an oversew (SFEEA-O)] revealed no differences between the techniques tested in cooled canine cadaveric jejunum (Fealey et al, 2020), although other authors following ex vivo testing of hand-sutured versus circular stapled anastomosis in canine large intestine concluded that end-to-end colonic anastomoses closed with circular stapler leaked at lower pressures than hand-sutured anastomoses (Sapora et al, 2021). Vicryl is commonly used for intestinal anastomosis in humans with good published success and is popular in Europe for veterinary use.…”
Section: Survival and Complication Rates In Clinical Casesmentioning
confidence: 99%